Clinical Features and Remission Rates in Cushing’s Disease: A Comparison of MRI-Detectable and MRI-Undetectable Pituitary Adenomas - Uysal, Serhat; Sulu, Cem; Muradov, Ilkin; Sahin, Serdar; Gul, Nurdan; Soyluk Selcukbiricik, Ozlem; Kubat Uzum, Ayse; Unal Kocabas, Gokcen; Sarer Yurekli, Banu; Hacioglu, Aysa; Karaca, Zuleyha; Barburoglu, Mehmet; Korkmazer, Bora; Kizilkilic, Osman; Kadioglu, Pinar (Hormone and Metabolic Research, 2025)
We aimed to characterize the clinical features and remission rates of patients with Cushing’s Disease (CD) without magnetic resonance imaging (MRI) detectable pituitary adenoma compared to CD patients with MRI-detectable pituitary adenoma.All patients with adrenocorticotropic hormone (ACTH)-dependent Cushing’s syndrome (CS) without MRI-detectable pituitary adenoma underwent high-dose dexamethasone suppression test, corticotropin-releasing hormone stimulation test, and/or bilateral inferior petrosal sinus sampling (BIPSS). The diagnosis of CD in patients without MRI-detectable adenoma was confirmed when the results of dynamic testing and sampling concordantly indicated ACTH-producing adenoma.These patients were included in MRI-undetectable group. Patients with ACTH-dependent CS had pituitary adenoma≥6 mm and those with pituitary adenoma<6 mm but BIPSS findings indicative of CD were included in MRI-detectable adenoma group. The study included 60 patients without MRI-detectable adenoma and 74 patients with MRI-detectable adenoma. At presentation, patients without MRI-detectable adenoma were older [47 years (30.25–58) vs. 40.5 years (29–49), p=0.036]. Hypertension (65% vs. 47.3%), diabetes mellitus (58.3% vs. 39.2%), and cardiovascular disease (13.3% vs. 2.7%) were more common in patients without MRI-detectable adenoma (p=0.040, p=0.027, p=0.020; respectively). The transsphenoidal surgery as initial treatment was higher in the patients with MRI-detectable adenoma group (97.3% vs. 80%, p=0.001). Third-month remission (60.4% vs. 63.8%, p=0.700) after surgery, and remission rates in the last visit (65.3% vs. 79.7%, p=0.077) were similar between the two groups. Inconclusion, the absence of an MRI-detectable adenoma underscores the necessity for comprehensive management.
Keywords: Cushing’s disease; management; pituitary adenoma; sella imaging; transsphenoidal surgery